Development of the Energy Equity Epic Beef Cattle Fattening Business (Sengkang), Gilireng Subdistrict, Wajo Regency, South Sulawesi - Irma; Muallim; Irna; Abdul Muta Ali (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2026)
This study aims to formulate development strategies for the beef cattle fattening business at Energy Equity Epic (Sengkang), Gilireng District, Wajo Regency, South Sulawesi, using the SWOT analysis approach. Despite having strong potential, the business still faces internal challenges such as low farmer knowledge and limited public interest, as well as external threats like market competition and minimal government intervention. The analysis results indicate that SO, WO, ST, and WT strategies can be applied to optimize strengths, seize opportunities, minimize weaknesses, and address threats. WO and WT strategies focus on improving human resource capacity and public awareness, while SO and ST strategies emphasize the use of CSR funding, collaboration with academics, and strengthening market competitiveness. With the proper implementation of these strategies, the cattle fattening business is expected to improve productivity, expand its market, and contribute to national food security.